Effects of warming and litter positions on litter decomposition in a boreal peatland - Ma, Guobao; Wang, Xianwei; Sun, Xiaoxin; Wang, Shujie; Du, Yu; Jiang, Jingyi (Frontiers in Ecology and Evolution, 2022)
Litter decomposition is an important source of carbon accumulation in the permafrost peatlands. Climate warming has led to shrub expansions and accelerated litter mixing with soils and fluctuations in the water table. However, little is known about how changes in the position of the litter will affect litter decomposition under climate warming. To reveal the mechanisms of response of the location of litter in the soil and climate warming to litter decomposition in permafrost peatlands. Here, we selected the evergreen shrub, Chamaedaphne calyculata, and the deciduous shrub, Vaccinium uliginosum, from the permafrost peatlands of the Greater Hing’an Mountains, China. The leaf litter was placed on the soil surface (no-mixing) and mixed with the soil (soil-litter mixing), and then it was incubated for 124 days at 15°C (control) and 20°C (warming). Our results showed that warming significantly increased the CO2 emission rates of C. calyculata and V. uliginosum by 19.9 and 17.4%, respectively. When compared to no-mixing, the CO2 emission rates were reduced (not significantly) by 1.5 (C. calyculata) and increased 13.6% (V. uliginosum) with soil-litter mixing. Interestingly, soil-litter mixing suppressed the positive effect of warming on the CO2 emission rates relative to no-mixing, and the suppressing effects in the V. uliginosum subplot were stronger than those in the C. calyculata subplot. Specifically, warming significantly increased the CO2 emissions of C. calyculata by 27.4% under no-mixing but the increase decreased to 13.1% under soil-litter mixing. Similarly, warming induced significant increases in the CO2 emissions of V. uliginosum, with an increase of 38.8% under no-mixing but non-significant increases (1.9%) were observed under soil-litter mixing. The combination of the enzyme activities of β-1,4-glucosidase, β-1,4-xylosidase and β-D-1,4-cellobiosidase and laccase and phenolics explained more than 60.0% of the variability in the CO2 emissions of C. calyculata and V. uliginosum, respectively. Our study highlights the importance of litter positions in mediating the responses of litter decomposition to climate warming and shrub expansions in the northern peatlands.